Effects of tizanidine premedication on the duration of perioperative maintenance dose of vecuronium bromide - Oflezer, Ceyhan (Journal of Medical Science, 2022)
Aim. The aim of this study was to evaluate the effects of preoperative administration of tizanidine on the maintenance dose duration of the nondepolarizing muscle relaxant, i.e. vecuronium bromide.Material and Methods. This prospective clinical study was conducted in 30 adult male patients scheduled for elective inguinal hernia surgery. Patients were categorised into two randomised groups based on the premedication use. Group 1 included patients (n = 15) who received oral diazepam (Diazem) in the evening prior to the surgery, as well as meperidine (Dolantin) 1 mg/kg-1 (max. 50 mg) i.m. with 50 ml water by mouth 1 hour before the procedure. Group 2 comprised patients (n = 15) who were given oral tizanidine 4 mg in the evening before the surgery, as well as oral tizanidine 4 mg with 50 ml water 1 hour prior to the operation. The following parameters were recorded in both groups: pre-operative and perioperative diastolic arterial blood pressure, systolic arterial blood pressure, mean arterial blood pressure, heart rate, respiratory rate, pre-operative vecuronium bromide maintenance doses, procedure time and postoperative score according to the Ramsay scale in 1st, 2nd and 3rd hour.Results. No significant difference was observed between the two groups with regard to the pre-operative and perioperative haemodynamic variables and the respiratory rate (P > 0.05), although it was found that vecuronium maintenance dose duration was significantly higher in the tizanidine premedicated group (P = 0.015). In addition, the operative time (P = 0.128) and the postoperative patients’ Ramsay scores did not differ statistically between the two groups (P > 0.05). Conclusions. The prolonged duration of vecuronium maintenance dose, the increased nondepolarizing block time, as well as haemodynamic stability preservation in patients undergoing inguinal hernia surgery following preoperative oral administration of tizanidine support the view that tizanidine can be used as an effective and safe myotonolytic premedication agent.